Memayu Hayuning Bawana’s Effect in Enhancing Human Resource Performance: The Effect of Employee Interaction and Value-Based Leadership - Sri Aningsih; Heri Wijayanto; Riawan Riawan; Sri Hartono (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Human resource management in educational institutions requires a comprehensive approach that goes beyond administrative functions, incorporating values, social relationships, and organizational culture. This study aims to analyze the influence of employee interaction and value-based leadership on human resource performance, as well as examine the moderating role of the Javanese philosophical value memayu hayuning bawana. Using a quantitative method, the study involved a saturated sample of 113 educators and staff in Muhammadiyah schools in Pacitan. Data were analyzed using PLS-SEM through assessments of the outer model, inner model, significance tests, and predictive evaluation. The results indicate that employee interaction and value-based leadership significantly and positively affect human resource performance, with value-based leadership showing a stronger influence. The moderating effect of memayu hayuning bawana was found to be positive but relatively small. The result implies that integrating local cultural values strengthens leadership practices and enhances organizational effectiveness. In conclusion, the combination of interpersonal interaction, value-based leadership, and local wisdom contributes significantly to improving human resource performance in educational institutions.